Simple Patent Protection: A Case of Sarung Tenun Goyor Indonesia and The Comparison to Malaysia Utility Innovation Protection (Universitas Negeri Semarang, 2022)
The work or products of SMEs are important for the protection of intellectual property rights. The Sarung Tenun Goyor in its production process has gone through long ideas and experiments to produce a distinctive motif and shape, but it becomes a problem whether a traditional work can be subjected to simple patent protection and instead ignores social values ​​and the value of community justice. In addition, Malaysia also has certain protection for utility innovalition that close to simple patent protection in Indonesia. This study is intended to analyze the simple patent protection in the case of Sarung Tenun Goyor Indonesia and Malaysia Utility Innovation Protectopn. This study showed that to fulfill the novelty element, development of the existing production process could be carried out while still paying attention to the values ​​of justice, social, and propriety. The fulfillment of Access Benefit Sharing stipulated in Law Number 13 of 2016 concerning Patents provides legal certainty of simple patent protection derived from traditional knowledge. Whereas the production process of the Sarung Tenun Goyor can be said to be a form of intellectual property and fulfills the elements as a simple patent object. The conclusion of this research is that the production process of the Sarung Tenun Goyor has not received legal protection. The Patent Law provides legal certainty for the development of the sarung tenun goyor production process by fulfilling Access Benefit Sharing (ABS).